(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The author explores the Bible motifs in Edward Albee’s play «A Delicate Balance». Over the past few decades the theme of religiosity in literature has acquired special significance in connection with the rethinking of Christian values in the postmodernism. Edward Albee’s play «A Delicate Balance» defined in many ways the Christian theme in the work of American playwright which contradicted the established opinion of domestic literary critics about the incompatibility of Albee’s plays with the ideas of Christianity. The author conducts a conceptual analysis of the New Testament and Old Testament plots (the parable of the Good Samaritan and the story of Tobias from the Book of Tobit) and their interpretation in the drama. The author focuses on the intertextuality of the postmodern text: its cento form (allusions, parodies, paraphrases), the features of presence of the biblical text in the text of the play. Consequently, the article shows the distorted representation of the idea of brotherly love on the example of the interpretation of the parable about the Good Samaritan and the story about Toby. It is underlined that Edward Albee’s work is a continuation of the tradition established in American literature, including didactic and prophetic (messianic) principles. Key words: Edward Albee; «Delicate Balance»; biblical text; postmodern text; the parable of the Good Samaritan; the book of Tobit. DOI 10.18522/1995-0640-2020-3-130-138